2015
DOI: 10.1103/physrevb.92.235409
|View full text |Cite
|
Sign up to set email alerts
|

Understanding double-resonant Raman scattering in chiral carbon nanotubes: Diameter and energy dependence of theDmode

Abstract: We present a theoretical model to describe the double-resonant scattering process in arbitrary carbon nanotubes. We use this approach to investigate the defect-induced D mode in CNTs and unravel the dependence of the D-mode frequency on the CNT diameter and on the energy of the resonant optical transition. Our approach is based on the symmetry of the hexagonal lattice and geometric considerations, hence the method is independent of the exact model that is chosen to describe the electronic band structure or the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…This result strongly supports the assignment of the IFM origin in prior studies. , In particular, one of those studies concluded that the IFM originates from an acoustic-like phonon mode with a K-momentum-like D-mode . In that prior analysis, the momentum of the IFM was determined from the well-known facts that the optical absorption of SWCNTs is enhanced by a van-Hove singularity and that elastic scattering is caused at defects. , However, the synchronous change shown in Figure a provides additional experimental support for the assignment of the IFM momentum. The effects of defect creation on the IFM were already assessed in the prior study, but the synchronous changes in the IFM and D-mode intensities were not reported …”
Section: Results and Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This result strongly supports the assignment of the IFM origin in prior studies. , In particular, one of those studies concluded that the IFM originates from an acoustic-like phonon mode with a K-momentum-like D-mode . In that prior analysis, the momentum of the IFM was determined from the well-known facts that the optical absorption of SWCNTs is enhanced by a van-Hove singularity and that elastic scattering is caused at defects. , However, the synchronous change shown in Figure a provides additional experimental support for the assignment of the IFM momentum. The effects of defect creation on the IFM were already assessed in the prior study, but the synchronous changes in the IFM and D-mode intensities were not reported …”
Section: Results and Discussionsupporting
confidence: 82%
“…In this case, the coefficient for the inverse diameter is 227 cm –1 ·nm, which is in good agreement with prior studies. , The other peaks do not show a systematic effect of diameter on the Raman frequency. Although the D-mode frequency was expected to vary systematically with diameter based on previous reports, , the range over which the D-mode varied was less than 12 cm –1 wide; therefore, the variation of this mode was not as significant as that of the IFM. This difference is clearly because the D-mode is associated with the optical phonon mode of graphene, while the IFM originates from an acoustic-like phonon mode. , …”
Section: Results and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A simulation of the (2)D-mode diameter dependence in nanotube ensembles and a description of the curvature induced jump between the optical transitions can be found in Ref. [40]. Ref.…”
mentioning
confidence: 99%
“…Recently, a step towards the understanding of the defectinduced D mode in nanotubes vs diameter and energy has been made using the hexagonal symmetry of graphene and geometrical considerations. 12,13 This approach allows assigning the two-phonon bands to pairs of definite phonons. However, the two-phonon band shape can only be predicted, taking into account the couplings and the electronic linewidth, and carrying out full integration over the Brillouin zone.…”
Section: Introductionmentioning
confidence: 99%